Direction and strategy of islamic education ministry of religious affairs of Indonesia - Sahri, Sahri; Syafi'i, Asrof; Sokip, Sokip (Universitas Islam Nahdlatul Ulama Jepara, 2023)
The above policies and strategies are efforts by the Ministry of Religious Affairs to improve the quality and relevance of Islamic religious education in Indonesia, so as to create a young generation with noble character, knowledge, and global competitiveness. This study uses a qualitative method, using a library research approach. In literature research, researchers collect data from written sources such as books, journals, articles, reports, and other documents related to the research topic. The resulting data is then analyzed using content analysis techniques or content analysis. The Indonesian Ministry of Religious Affairs has several policies and strategies in the development of Islamic religious education, including: 1)Development of an Islamic Religious Education curriculum that is adaptive, relevant, and in accordance with the demands of the time,2) Improve the quality and quantity of Islamic Religious Education teachers through training and skill development programs. 3) Development and improvement of the quality of Islamic Religious Education learning media, 4) Increase the role of the family in fostering Islamic religious education through family religious education programs, 5) Provision of scholarships for students and students who excel in the field of Islamic religious education, 6) Provision of adequate and sustainable Islamic religious education facilities and infrastructure